Apoptosis mediated by crosstalk between mitochondria and endoplasmic reticulum: A possible cause of citrinin disruption of the intestinal barrier - Yuanyuan Li; Yongkang Wang; Zonghan Jiang; Chenglin Yang; You Wu; Aoao Wu; Qike Zhang; Xiaofang Liu; Bo Xiao; Yiya Feng; Jing Wu; Zengenni Liang; et al. (Ecotoxicology and Environmental Safety)
Citrinin (CTN) is a mycotoxin commonly found in contaminated foods and feed, posing health risks to both humans and animals. However, the mechanism by which CTN damages the intestine remains unclear. In this study, a model of intestinal injury was induced by administering 1.25 mg/kg and 5 mg/kg of CTN via gavage for 28 consecutive days in 6-week-old Kunming mice, aiming to explore the potential mechanisms underlying intestinal injury. The results demonstrate that CTN can cause structural damage to the mouse jejunum. Additionally, CTN reduces the protein expression of Claudin-1, Occludin, ZO-1, and MUC2, thereby disrupting the physical and chemical barriers of the intestine. Furthermore, exposure to CTN alters the structure of the intestinal microbiota in mice, thus compromising the intestinal microbial barrier. Meanwhile, the results showed that CTN exposure could induce excessive apoptosis in intestinal cells by altering the expression of proteins such as CHOP and GRP78 in the endoplasmic reticulum and Bax and Cyt c in mitochondria. The mitochondria and endoplasmic reticulum are connected through the mitochondria-associated endoplasmic reticulum membrane (MAM), which regulates the membrane. We found that the expression of bridging proteins Fis1 and BAP31 on the membrane was increased after CTN treatment, which would exacerbate the endoplasmic reticulum dysfunction, and could activate proteins such as Caspase-8 and Bid, thus further inducing apoptosis via the mitochondrial pathway. Taken together, these results suggest that CTN exposure can cause intestinal damage by disrupting the intestinal barrier and inducing excessive apoptosis in intestinal cells.